2014
DOI: 10.2522/ptj.20120525
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 2 Activity Monitors in Detecting Steps in People With Stroke and Traumatic Brain Injury

Abstract: The Fitbit Ultra may be a low-cost alternative to measure the stepping activity in level, predictable environments of people with stroke and TBI who can walk at speeds ≥0.58 m/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 45 publications
9
124
0
Order By: Relevance
“…The major downside of these devices is the limited set of features they provide: number of steps taken, distance walked, energy expenditure (kcal) and sleep duration. Moreover, the quality of information they provide is usually not satisfactory, as revealed for example by the following studies: Fitbit Ultra 5 is found to have fair to good accuracy in identifying steeping activity for stroke and TBI patients [42] with an Intraclass Correlation Coe cient (ICC) of 0.73, and for healthy subjects agreement was above 95% [68]. The same study found Nike+ Fuelband 6 to have an ICC of 0.2.…”
Section: Wearable Sensor-based Armentioning
confidence: 99%
“…The major downside of these devices is the limited set of features they provide: number of steps taken, distance walked, energy expenditure (kcal) and sleep duration. Moreover, the quality of information they provide is usually not satisfactory, as revealed for example by the following studies: Fitbit Ultra 5 is found to have fair to good accuracy in identifying steeping activity for stroke and TBI patients [42] with an Intraclass Correlation Coe cient (ICC) of 0.73, and for healthy subjects agreement was above 95% [68]. The same study found Nike+ Fuelband 6 to have an ICC of 0.2.…”
Section: Wearable Sensor-based Armentioning
confidence: 99%
“…Furthermore, during the performance of a circuit of activities of daily living, the device significantly underestimated activity time but provided an acceptable estimation of EE in a group basis. 36 The StepWatch Activity Monitor (SAM) (Orthocare Innovations, Seattle, WA) is an accelerometer worn on the ankle that measures step counts from all walking. The step counts from SAM, validated against manual counts, proved to have an accuracy >90% in 99% of 127 COPD patients.…”
Section: New Motion Sensors Used For Pa Measurement In Copdmentioning
confidence: 99%
“…We need to consider the security measure that how we can utilize the personal data without causing any security bleach [4]. In this architecture, we have four stages and in the first stage, we have a sensor which will trap the all the data from the surrounding environment, in the second stage, we have a middleware like a data converter which will convert the data captured by the sensor into human readable language which will be having the combination of IoT and ML.…”
Section: Introductionmentioning
confidence: 99%